Beyond usefulness: unveiling the factors driving visitor acceptance of technology in sports museums - Coskun, Aysen; Oncul, Ugur (Emerald Group Publishing Ltd, 2026)
PurposeMuseums serve as vital custodians of cultural heritage and knowledge, yet regardless of their type, museums have continuously adopted technological advancements to meet visitor expectations and improve their experiences. This study aims to investigate how sports museum visitors accept technological advances through an extended Technology Acceptance Model (TAM) incorporating compatibility, perceived enjoyment and visitor satisfaction.Design/methodology/approachData were collected via a computer-assisted personal interview technique from 271 visitors at the Besiktas JK Museum, a sports museum located in T & uuml;rkiye.FindingsThe findings indicate the significance of perceived usefulness in shaping visitors' technology usage intention in museum visits, while also highlighting the importance of compatibility and perceived enjoyment.Practical implicationsThe study underscores the need for sports museums to align technology with visitor needs and experiences, ensuring enjoyable and meaningful interactions. Sports museums should focus on making technology both useful and enjoyable to enhance visitor satisfaction and encourage technology adoption during visits.Originality/valueThis study contributes to the literature by enhancing the understanding of technology acceptance in sports museums by identifying factors beyond traditional TAM constructs. It provides a nuanced understanding of how technological advancements are accepted by sports museum visitors.
Keywords: Museum; Sports museum; Compatibility; Perceived enjoyment; Visitor satisfaction; Technology acceptance model